Accreditation Policy and Quality of Higher Education - Imam Muhayat (Al-Hayat Al-Istiqomah Foundation, 2018)
Accreditation policy is nothing but a form of quality control of universities. Accreditation activities assess the independence of the universities concerned. Accreditors assume that human action is determined by self-will (self-termination), and on self-direction. The substance of quality and accreditation is more on building a new scientific paradigm. In the context of achieving quality refers to the concept of individual - institutional motivation in carrying out the work. The recognition of more important identity is to change the paradigm and epistemology of science in accordance with the development and demands of the times. New, more representative facilities are built. New educational equipment and media are also being held. All of that form has fulfilled the instrument of quality assurance of the universities. The answer that can parse the problem is the policy of accreditation. Accreditation is interpreted as a measure of quality assurance. The objective of achieving the quality can be realized based on the strengthening of the strategy and quality technique pursued through accreditation, until the supervision is interpreted as a challenge that needs to be answered completely. The real phenomenon of action and reality in the environment of university is a careful step in writing this paper, the academic environment service; The principle of managerial optimization; an input-output perspective - a multidimensional outcome; principles of harmonizing institutional governance, and risk reduction principles. These five principles become a system that binds the strengthening of accreditation policies implicate the quality of the university.Kebijakan akreditasi tidak lain sebagai wujud pengawasan mutu perguruan tinggi (PT). Akreditor menilai tindakan kemandirian PT bersangkutan. Ia selalu berasumsi bahwa tindakan manusia ditentukan oleh kemauan sendiri (self ditermination), dan pada tujuan sendiri (self direction). Substansi mutu dan akreditasi lebih pada membangun paradigma baru keilmuan. Dalam konteks pencapaian mutu mengacu konsep motivasi individual–institusional dalam melaksanakan pekerjaan. Penghargaan akan identitas yang lebih penting adalah mengubah paradigma dan epistemologi keilmuan yang sesuai dengan perkembangan dan tuntutan zaman. Fasilitas-fasilitas baru yang lebih representatif memang dibangun. Peralatan dan media pendidikan yang baru juga diadakan. Semua itu wujud telah terpenuhinya instrumen penjaminan mutu PT. Adapun jawaban yang dapat mengurai permasalahan itu adalah kebijakan akreditasi. Akreditasi dimaknai sebagai langkah penjaminan mutu. Tujuan pencapaian mutu dapat diwujudkan atas dasar penguatan strategi dan teknik mutu yang diupayakan melalui akreditasi, hingga pengawasan dimaknai sebagai tantangan yang perlu dijawab secara tuntas. Fenomena aksi dan realitas yang senyatanya di lingkungan PT merupakan langkah pencermatan dalam penulisan makalah ini, yaitu pelayanan lingkunganakademik; Prinsip optimasi manajerial; perspektif inputâ€”output–outcome multidimensional; prinsip harmonisi tata kelola institusi, dan prinsip pengurangan risiko. Kelima prinsip tersebut menjadi sebuah sistem yang mengikat sebagai penguat kebijakan akreditasi berimplikasi mutu PT.